Start-up research universities, high aspirations in a complex reality: a Russian start-up university case analysis using stakeholder value analysis and system dynamics modeling - Raafat M. Zaini; Dmitriy E. Lyan; Eric Rebentisch (Triple Helix, 2015)
There have been several initiatives by the governments in different parts of the world to establish world-class universities (WCUs). Such initiatives have been attempted only several times and yielded varied results. This article contributes to the existing body of research in architecting WCUs by presenting an operational strategic modeling framework that is grounded in the existing body of literature for developing WCUs (Salmi 2009) which can be used to test assumptions, reveal strategic levers, and analyze dynamic complexity inherent in a task of scaling a start-up university. We present a research study that leveraged stakeholder analysis and system dynamics modeling to architect and test a long-term strategic plan of scaling a newly created Skolkovo Institute of Science and Technology (SkolTech) in Moscow, Russia. We find that the existence of patient capital and favorable governance is conditional on university leadership's ability to effectively manage stakeholder expectations, maintain high-quality standards of its faculty and student population, and protect its brand of a world-class institution. We argue that the operational framework and findings derived from the case of SkolTech can be generalized and applied to other efforts in that area.
Keywords: 330; Innovation; Entrepreneurship; Economic development; Higher education; Modeling and simulation; Strategy; System dynamics